Implementation of Sustainable Operations Management in the Digital Age: Toward a Greener and More Efficient Business - Fahmil Fahmil; Andi Muhammad Rivai; Ahmad Rifai; Muhammad Rivalgy (Journal of Economics, Entrepreneurship, Management Business and Accounting, 2024)
This study explores the importance of sustainable operations management in the digital age. The research aims to examine how digital transformation has reshaped various industrial sectors, particularly in the context of green business practices, sustainability-focused technology and innovation, and the development of sustainable products and services. Additionally, it includes a case study on the implementation of sustainable operations management by Unilever. The research methodology involved a literature review of relevant sources, including scholarly journals, reports, and recent articles. A descriptive analysis technique was employed to identify trends, challenges, and opportunities in applying sustainable operations management in the digital era. The findings reveal that digital transformation has significantly impacted multiple industries. Companies that adopt green business practices, leverage technology for sustainability, and innovate sustainable products and services can enhance their triple bottom line performance and gain a competitive advantage in the market. The Unilever case study illustrates how embracing green digitalization tools and integrating sustainability into all operations can help organizations achieve their sustainability goals. However, the study also highlights the challenges and opportunities that must be navigated when implementing sustainable operations management in the digital age.